The differences in the secretarial job functions and competencies between public and private sector in Kinta Valley, Perak / Nordayana Zulkifli, Rohana Ehsan and Zulkefli Abd. Rahman - Zulkifli, Nordayana; Ehsan, Rohana; Abd. Rahman, Zulkefli (2012)
This study was conducted to identify the differences of the secretarial job functions and competencies between public and private sectors in Malaysia. From the results obtained, the much needed changes to improve the implementations of public sector service and productivity are also examined and suggested for improvement. The scope of the study was the secretarial staffs in the public and private sector employed in Ipoh, Kinta Valley, Perak. The secretarial staffs' position in the public sector is under the title Administrative Assistant (Secretarial). A set of questionnaires consisted of close-ended questions was used to gather the needed information. The main instruments used for this study is the questionnaire. The questionnaires were tested for face and content validity. The questionnaires were personally distributed to all the respondents in the public and private sectors in Ipoh, Perak and specific time was given for them to answer them. From the results obtained via questionnaires, the finding shows that there are significant differences in the job functions and job competencies aspects between the public sector and private sector. Most of the respondents agreed regarding the significance of job qualification which consists of skills, knowledge and abilities (SKA's) to perform job functions. It was also found that several aspects such as the secretarial job governance are discussed and emphasized. Finally, the discussion retrieved from the data analysis suggested several recommendations include the perspective of change to the public sector from the relevant and revised entry level requirements, salary scheme restructuring, career advancement opportunities and the systems to improve and organized the secretarial job functions within the public sector organizations based on the successful story and criteria implemented by the private sector organizations.